THE RELATION OF SCIENCE AND RELIGION - TAUFIK RIZKI SISTA; Aulia Faramitha (Pondok Pesantren Modern Islam Assalaam, 2022)
This study aims to describe the relation of science and religion according to BJ. Habibie and KH. Imam Zarkasyi and the similarities and differences among the thought. The type of this research is literature research with descriptive qualitative approach and biographical history. Data collection techniques using documentation and interview techniques. While the data analysis technique uses content analysis, descriptive and comparative. The results of this study are based on the thoughts of BJ. Habibie and KH. Imams have the same opinion, including (a) Al-Quran is a source of knowledge (b) seeking knowledge for worship (c) Educational institutions are a forum for forming quality human beings (d) Religion tolerates science. According to BJ. Habibie (a) religion as a counterweight (b) Implementation of the Koran for technological findings guidelines (c) is more inclined to the application of technology, Meanwhile, according to KH. Imam Zarkasyi: (a) religion as a remedy for discord (b) Implementation of the Al-Qur’an in the application of the Five Souls of Pondok Modern (c) not inclined and applies knowledge in a balanced way